Selenomethionine alleviates LPS-induced septic kidney injury by regulating mitochondrial dynamics changes - Zhou, Xu; Zhao, Jiling; Cheng, Wusong; Chen, Su; Zhang, Ya; Qu, Yangang; Hu, Xiaohui; Lan, Yong; Tu, Qimin; Hu, Jiaxin; Chen, Hongbo (Frontiers in Pharmacology, 2025)
BackgroundAcute kidney injury (AKI) is a prevalent complication of sepsis, where the inflammatory response plays a crucial role. Selenium exhibits anti-inflammatory and antioxidant properties, but its impact on sepsis-induced AKI remains unclear.Methods and resultsIn this study, we used a lipopolysaccharide (LPS)-induced murine model of sepsis-associated acute kidney injury (SA-AKI) in male C57BL/6 mice (8–12 weeks old) to investigate the protective mechanisms of selenomethionine (SeMet). Mice received weekly oral administration of SeMet (0.375 mg/kg) commencing 1 week prior to AKI induction. Our results demonstrated that SeMet treatment significantly attenuated the inflammatory response, reduced oxidative stress, and ameliorated renal pathological damage compared to saline-treated controls. Mechanistic investigations revealed that SeMet modulates altered mitochondrial dynamics and suppresses the NF-κB signaling pathway, thereby promoting macrophage polarization toward the anti-inflammatory M2 phenotype.ConclusionThese findings collectively demonstrate that SeMet effectively mitigates inflammation and ameliorates sepsis-induced AKI, suggesting its potential as a therapeutic candidate for SA-AKI prevention and treatment.